Współpraca państw członkowskich UE w sprawach cywilnych w obszarze poszukiwania prawa właściwego zobowiązaniom pozaumownym w latach 1957–1997 - Wasylkowska-Michór, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article focuses on a historical overview of the evolution of cooperation on civil matters in the European Union. Given the fact that this cooperation has developed the best in international private law, the author presents its development, using as her example legislative work on the harmonisation of confl ict-of-law rules regarding tort, which in the end led to the adoption of the Rome II Regulation on the law applicable to non-contractual obligations. The article is divided into three parts corresponding to the stages in the development of cooperation between member states in civil matters — after the entry into force of the EEC Treaty, then after the entry into force of the Maastricht Treaty and fi nally the entry into force of the Treaty of Amsterdam.
Keywords: współpraca w sprawach cywilnych; Traktat EWG; Traktat z Maastricht (1992); Traktat z Amsterdamu; delikt; prawo prywatne międzynarodowe